PENDAMPINGAN PEMBACAAN AL-QUR’AN IQRO DAN AL-QUR’AN UNTUK MENINGKATKAN KUALITAS BACAAN SISWA-SISWI KELAS 6 DI MIS DARUL ULUM PALANGKA RAYA - Wulantika Purnama; Istiyati Mahmudah (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of writing this community service article is to provide assistance to students in reading Iqro and the Qur'an in order to improve the quality of reading in accordance with the rules of tajwid science. MI Darul Ulum Palangka Raya City has its own challenges, namely that there are still many students who are not fluent in reading Iqro and the Qur'an so that they require intensive teaching. Assistance in reading Iqro and the Qur'an with tajwid to improve the quality of students' reading with the Asset Based Community Development (ABCD) method is an appropriate solution in order to develop the assets that each student already has. This community service aims to explore the effectiveness of this assistance in the context of improving the quality of students' reading in reading Iqro' and the Qur'an. The ABCD method is used as a framework, where this approach emphasizes the use of local potential and resources available in the community to overcome problems. Assistance is carried out by several students who are not yet fluent in reciting the Koran to support the assistance activities for reading Iqro' and the Qur'an with tajwid. The results of the community service show that mentoring the reading of Iqro and the Qur'an with tajwid is able to improve the quality of students. MI Darul Ulum Palangka Raya. The existence of this community service program is to be more intense in teaching students to read Iqro' and the Qur'an, and to make students more enthusiastic to continue learning routinely every day to develop the quality of their reading in reading Iqro' and also the Qur'an. With the ABCD method, mentoring the reading of Iqro' and the Qur'an has opened up opportunities for teachers and students to improve the quality of religious learning, as well as empowering local communities in facing educational challenges.